Diagn Interv Radiol 2021
DOI: 10.5152/dir.2021.21011
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling surgery after transarterial embolization: does timing make any difference to intraoperative blood loss for renal cell carcinoma bone metastases?

Abstract: Renal cell carcinomas (RCCs) are one of the leading causes of cancer-related death worldwide (1). About one-third of RCCs are metastatic at initial diagnosis, and skeletal metastases are the second most frequent type of RCC metastases following lung metastases (43%) (2, 3). Surgical intervention is an option for the treatment of skeletal metastases of RCCs. Although local ablative therapies like thermal ablation may be preferred for tumors <3 cm, systemic chemotherapy and radiotherapy are other options for sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…10,[14][15][16][17][18] Our analysis sought to evaluate how the timing between embolization and surgery impacts peri-operative outcomes in Previous analyses have evaluated how different time intervals between embolization and surgery impacts blood loss and the risk of transfusion peri-operatively with mixed evidence reported in the literature. 4,[7][8][9]16 In their analysis of 66 patients with hypervascular spinal metastases, Kato et al found significantly higher blood loss days after embolization (2000 [600-2500]; p = 0.002). 4 Conversely, Sun et al found no differences in EBL between patients undergoing surgery within 24 h and those waiting greater than 36 h from embolization (575 vs. 402 mL; p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,[14][15][16][17][18] Our analysis sought to evaluate how the timing between embolization and surgery impacts peri-operative outcomes in Previous analyses have evaluated how different time intervals between embolization and surgery impacts blood loss and the risk of transfusion peri-operatively with mixed evidence reported in the literature. 4,[7][8][9]16 In their analysis of 66 patients with hypervascular spinal metastases, Kato et al found significantly higher blood loss days after embolization (2000 [600-2500]; p = 0.002). 4 Conversely, Sun et al found no differences in EBL between patients undergoing surgery within 24 h and those waiting greater than 36 h from embolization (575 vs. 402 mL; p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9]16 In their analysis of 66 patients with hypervascular spinal metastases, Kato et al found significantly higher blood loss days after embolization (2000 [600-2500]; p = 0.002). 4 Conversely, Sun et al found no differences in EBL between patients undergoing surgery within 24 h and those waiting greater than 36 h from embolization (575 vs. 402 mL; p > 0.05). 10 This was further seen in the analysis by Tang et and transfusion requirement between patients undergoing surgery the same day as embolization compared with those undergoing surgery the following day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraoperative blood loss was lower with complete vs partial embolization (mean ± standard deviation, 809 ± 835 vs. 1210 ± 904 mL, p = 0.03); among patients with complete embolization, intraoperative blood loss was lower if the surgery was performed on the same day of the embolization [ 35 ]. Another recent study that included 41 patients with spinal and extra-spinal renal cell carcinoma metastases suggested that preoperative embolization was more effective in reducing blood loss when surgery was scheduled on the same day of the embolization [ 36 ]. Clausen et al conducted a randomized controlled trial including 45 patients with metastases of the spine from variable primary cancers, 23 of whom received preoperative embolization and 22 surgery without preoperative embolization.…”
Section: Embolizationmentioning
confidence: 99%